Esclavitud, racialización e identidades africanas en los registros parroquiales republicanos de Cartagena de Indias y Caracas de principios del XIX - Estaba Amaiz, Roraima (Jahrbuch für Geschichte Lateinamerikas, 2025)
Racializing narratives were in force both in the Spanish Ancien Régime and in the later Spanish-American republics during the first half of the 19th century. Counterintuitively, in the official discourse, the colonial and republican authorities of Colombia and Venezuela converged in the use of ideological devices of control and sociorracial classification aimed exclusively at the enslaved black population and, in this sense, reproduced slave-owning thinking. Nor did the local sphere escape this racializing logic. The parish slave registries of Cartagena de Indias and Caracas, for instance, reproduced these racializing narratives until the republics of Colombia and Venezuela were well consolidated in the mid-19th century, and were decisive for the hierarchization of the social body and the delimitation of the political community. From a comparative perspective of two (post)colonial spaces of the Spanish Afro-Atlantic world, Colombia and Venezuela, this article analyzes the (re)construction of African identities in these racializing narratives, in light of the parish records of Cartagena de Indias and Caracas during the first decades of the nineteenth century.